Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair And Share dan Sikap Siswa Tentang Mata Pelajaran Ekonomi terhadap Hasil Belajar Siswa Kelas X Sman 1 Kec. X Koto Diatas - Junita Karnila; Yulhendri Yulhendri (Program Magister Pendidikan Ekonomi (S2), 2014)
The Economic learning results obtained of the first grade students in SMAN 1 X Koto Diatas was still low. This was occurred because of teacher-centered method in the teaching and learning process and also students’ negative attitude about this subject. One of the efforts that can be done to solve this problem is by using cooperative learning model type Think Pair and Share. The study aimed at findings (1) The Effects of Cooperative Learning Model Type Think, Pair and Share (TPS) toward students’ Economic learning results, (2) The Effects of Students’ Attitudes about Economic Subject toward students’ learning results, (3) The interaction between the Learning Model and Students’ Attitudes on Economic Lesson toward Economics Learning results. The type of this research is a Quasi-experiment and the population was the students of grade X IS of SMA Negeri 1 X Koto Diatas. The sampling technique was purposive sampling which grade X IS1 as the experimental class and grade X IS2 as the control class. The type of data consisted of primary data and secondary data, while the data analysis was descriptive and inductive analysis by using two-ways of ANOVA. The results of the study are (1) the students who are taught by Think Pair and Share models had significantly higher learning outcomes than them whom are taught by conventional models, (2) the students who have positive attitudes about Economic subject had significantly higher learning outcomes than them whom have negative attitudes about this subject and (3) There is no interaction between the learning model with the students' attitudes on this subject toward the students’ learning outcomes. Keywords: Think Pair and Share models, students’ attitudes toward economic subject, students learning result in the subject of Economy